1997
DOI: 10.1097/00004728-199709000-00025
|View full text |Cite
|
Sign up to set email alerts
|

Synovial Sarcoma: Frequency of Nonaggressive MR Characteristics

Abstract: There are two sets of MR features seen with synovial sarcoma. Small lesions of -5 cm can demonstrate a nonaggressive appearance with well circumscribed margins and homogeneous signal intensity. These tumors could be confused with benign lesions, resulting in inappropriate surgical intervention like excisional biopsies through transverse incisions. This would make future surgery more difficult. Larger lesions tend to be more heterogeneous in signal intensity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(46 citation statements)
references
References 8 publications
2
44
0
Order By: Relevance
“…14b, c). Small tumors, less than 5 cm, present a more homogenous intensity signal [50] and may be confused with benign lesions, especially if their margins are well defined [49,50]. Synovial sarcoma shows intense but heterogeneous gadolinium enhancement (Fig.…”
Section: Synovial Sarcomamentioning
confidence: 99%
See 1 more Smart Citation
“…14b, c). Small tumors, less than 5 cm, present a more homogenous intensity signal [50] and may be confused with benign lesions, especially if their margins are well defined [49,50]. Synovial sarcoma shows intense but heterogeneous gadolinium enhancement (Fig.…”
Section: Synovial Sarcomamentioning
confidence: 99%
“…Synovial sarcoma shows intense but heterogeneous gadolinium enhancement (Fig. 15b), which may help to differentiate these small homogeneous tumors from benign cystic lesions [50].…”
Section: Synovial Sarcomamentioning
confidence: 99%
“…Currently, 9 cases of intra-articular SS have been reported with specific MRI findings [25][26][27][28][29][30][31][32][33][34][35][36].…”
Section: Staging Treatment and Follow-upmentioning
confidence: 99%
“…Initially, these cases were mistaken for benign lesions on imaging studies and even on intraoperative frozen section analysis in Case 1. In fact, mistaking this sarcoma for a benign entity has happened with nearly every reported case of intra-articular SS in the current literature [11,[25][26][27][28][29][30][31][32][33][34]. The most recent case report from Freidman, et al in 2013, demonstrated failure to consider malignancy in a 26-year-old man with a 2.7 cm intra-articular knee mass that led to a misdiagnosis of PVNS and subsequent arthroscopic resection as in Case 2 presented here-in [11].…”
Section: Staging Treatment and Follow-upmentioning
confidence: 99%
“…Synovial sarcoma, when small, is often mistaken for a ganglion cyst or bursitis due to its homogeneous high signal on T2-W imaging, smooth, rounded appearance, and position near the joint [ 74 ]. It is the malignant lesion most likely to be misdiagnosed as benign [ 5 ].…”
Section: Imagingmentioning
confidence: 99%